1978
DOI: 10.1037/0096-1523.4.3.380
|View full text |Cite
|
Sign up to set email alerts
|

Auditory streaming is cumulative.

Abstract: The auditory system appears to begin listening to an input with a bias toward hearing the input as a single stream, but it gradually accumulates evidence over a period of seconds which may lead to the input's being split into substreams. Several seconds of silence or of unpatterned noise slowly remove the bias of the mechanism in favor of these streams. These effects were demonstrated in experiments in which young adult listeners sped up sequences of tones until they split. The sequences varied in the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
273
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(303 citation statements)
references
References 8 publications
26
273
4
Order By: Relevance
“…This suggests that when listeners were actively trying to segregate sounds in the current study, stream segregation occurred almost instantaneously after the start of the stimulus sequence. Under these conditions, the segregation "build-up" effect, which has been observed in other studies under neutral listening conditions (van Noorden 1975;Bregman 1978;Anstis and Saida 1985;Carlyon et al 2001;Cusack et al 2004;Micheyl et al 2005a;Pressnitzer et al 2008) and conditions that encouraged integration (Roberts et al 2008), appears to have. However, the lack of a significant effect of N in this experiment should not be interpreted as evidence that build-up effects cannot be obtained under conditions that promote stream segregation.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…This suggests that when listeners were actively trying to segregate sounds in the current study, stream segregation occurred almost instantaneously after the start of the stimulus sequence. Under these conditions, the segregation "build-up" effect, which has been observed in other studies under neutral listening conditions (van Noorden 1975;Bregman 1978;Anstis and Saida 1985;Carlyon et al 2001;Cusack et al 2004;Micheyl et al 2005a;Pressnitzer et al 2008) and conditions that encouraged integration (Roberts et al 2008), appears to have. However, the lack of a significant effect of N in this experiment should not be interpreted as evidence that build-up effects cannot be obtained under conditions that promote stream segregation.…”
Section: Resultsmentioning
confidence: 82%
“…Finally, based on the results of earlier studies, which showed that stream segregation usually "builds up" over time (van Noorden 1975;Bregman 1978;Anstis and Saida 1985;Carlyon et al 2001;Cusack et al 2004;Micheyl et al 2005a;Pressnitzer et al 2008), we expected the proportion of "two streams" responses to increase as a function of sequence length. Instead, relatively large proportions of "two streams" responses were observed in response to short stimulus sequences that contained only two triplets, as long as the frequency separation was relatively large.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The build-up of stream segregation When a long sound sequence is presented with an intermediate difference between the sounds in the sequence, the tendency for fission to occur increases with increasing exposure time to the tone sequence [15,16]. One interpretation of this is that the auditory system starts with the assumption that there is a single sound source, and fission is perceived only when sufficient evidence has built up to contradict this assumption.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 99%
“…It is what allows us to follow a conversation in a crowded restaurant, in the midst of other conversations, with music in the background and the sound of tinkling glasses. An essential feature of streaming is that it takes time: initially, subjects tend to group all of the acoustic information into one global stream [2,3]. When we first walk into the restaurant, the first impression may be of a 'loud and undifferentiated noise' [4].…”
Section: Introductionmentioning
confidence: 99%